Improvement of pak choi (Brassicca rapa var. chinensis) growth in acidic soil using fermented liquid organic fertilizer produced from unmarketable vegetables - M.P. Ramarao, Sanjeev (2023)
The Malaysian government is facing significant challenges related to managing food waste, a concern that contributes to greenhouse gas emissions in landfills. This waste, however, contains valuable nutrients that, when harnessed through fermentation, can yield liquid organic fertilizer (LOF). This fertilizer has the potential to enhance soil quality by addressing issues such as low cation exchange capacity, pH imbalances, and insufficient mineral nutrient content, directly impacting crop productivity. This research encompasses two primary experiments: the first involves characterizing the LOF derived from food waste collected from nearby wet markets, particularly unmarketable vegetables and fruits, which undergoes wet anaerobic fermentation in a 1:2 ratio with water. The second experiment aims to explore the impact of LOF on the growth and yield of pak choi vegetables. For experiment 1, the food waste derived from unmarketable vegetables and fruits was identified, collected from the nearest wet market, and fermented under wet anaerobic with a ratio of 1:2 (food waste: water). The food waste was fermented separately under three inducers: T2- yeast: T3- brown sugar, and T4- shrimp paste to boost the fermentation process and without inducer acting as a T1-control. Liquid organic fertilizers were sampled at 30 (30D), 45 (45D), and 60 (60D) days of fermentation and analyzed for nutrient content. These experiments were laid in a randomized complete block design (RCBD) and replicated three times. Results of the LOF derived from unmarketable vegetables through fermentation for 60 days using yeast as an inducer showed the highest nitrogen (0.95%), phosphorus (0.31%), and potassium (1.68%). Therefore, the LOF using yeast as an inducer was further for experiment 2. It consisted of seven treatments; T1- NPK (15-15-15) fertilizer; T2- 100% of LOF (30D); T3- 100% of LOF (45D); T4- 100% of LOF (60D); T5- 50% of LOF (30D) + 50% NPK; T6-50% of LOF (45D) + 50% NPK; and T7- 50% of LOF (60D) + 50% NPK. The experiment was arranged using Completely Randomized Design (CRD) with 5 replications. The findings from the second experiment revealed that soil treated with 50% LOF of 60D+ 50% NPK (T7) application was shown to give positive results in soil pH, cation exchange capacity (CEC), organic matter (OM), and soil catalase activity measured at the harvest stage which increased by 18.27%, 30.15%, 44.55%, and 5.26%, respectively compared to the before-harvest stage soil. Meanwhile, T7 also increases plant height, fresh weight, total chlorophyll, and total flavonoid content at 5.88%, 6.12%, 1.12%, and 0.25%, respectively. Besides, leaf area and dry weight were 46.36 cm2 and 0.88 g, respectively, which do not significantly different from standard fertilizer, Treatment 1. It can be concluded that the integration of organic and chemical nutrient inputs showed better results in providing a more balanced supply of nutrients.